Pengaruh.Kompetensi dan Profesionalisme Kerja.Terhadap Kinerja Pegawai.Pada Kantor Kelurahan Kayuringin Jaya Kota.Bekasi - Irwansyah, Iwan; Purwatomo, Purwatomo (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
One of the measures of success for an individual, Team, or Organization lies in its performance. If the performance is high or increases, the organization is considered successful. However, if it is lower than the standard or declines, it can be deemed as not optimal. The purpose.of this.study is to ascertain.how much employee competence affects employee performance at the Kayuringin Jaya Village Office in Bekasi City, to analyze how work professionalism affects Employee Performance, and to assess the combined influence of.Competence and Work Professionalism on Employee Performance. This.research employs a. quantitative method with a sample size of 40 respondents, utilizing Saturation Sampling (Census) technique. Data collection was conducted using questionnaires. Instrument testing, multiple.linear.analysis, hypothesis.testing, and classical assumption testing are all part of the study. The findings indicate.that at the Kayuringin Jaya Village Office in Bekasi City, competence has a positive and significant influence on employee performance of 0.761 or 76.1%. Work Professionalism also has a favorable and significant influence of 0.635 or 63.5% on Employee.Performance at.the same office. The total effect.of.competence.and.work professionalism on.employee.performance is 0.763, or 76.3%, which is good and significant.